Choosing undergraduate music performance program in UiTM Shah Alam / Zyzy Geofrey - Geofrey, Zyzy (2013)
The purpose of this study was to explore the reasons why undergraduate music performance majors choose this program as their degree study. The researcher conduct this research at Faculty of Music UiTM Shah Alam and asked them about the main reasons as to why they choose music performance as their pathway for undergraduate music program. Participant responses yielded qualitative data that the researcher coded and combines it in the following three themes: expectation, advantages and disadvantages, and influences. That is, students reported that they want to improve their playing on musical instrument, they want to learn the art of performing and influenced by their family. To build a better understanding about this research result, the researcher compare the result of the related research that find from journal and internet.